International Seminar: «Climate Change and its social and environmental repercussions » - Brito, Brígida (2014)
The International Seminar on "Climate change and its social and environmental repercussions" (“Alterações Climáticas e suas repercussões socio-ambientais”) took place from 20 to 23 August 2012 in Palácio dos Congressos, in the city of São Tomé, Democratic Republic of São Tomé and Príncipe. This meeting was organized by a group of nine public, private and civil society institutions acting in São Tomé and Príncipe, Portugal and Spain, in compliance with the principles of international partnership: Direção-Geral do Ambiente (DGA) and Direção das Florestas (DF) of the Democratic Republic of São Tomé and Príncipe; Observatório de Relações Exteriores, Universidade Autónoma de Lisboa (OBSERVARE, UAL); Instituto de Ciências Sociais da Universidade de Lisboa (ICS-UL); Universidad de Santiago de Compostela (USC), International Association of Investigators for Environmental Education (NEREA Investiga) and Associação Portuguesa de Educação Ambiental (AsPEA); Centro de Extensión Universitária e Divulgación Ambiental de Galicia (CEIDA); the NGO from S. Tomé and Príncipe Mar, Ambiente e Pesca Artesanal (MARAPA).